Isolation and enrichment of PC-3 prostate cancer stem-like cells using MACS and serum-free medium - SHENG, XIA (D.A. Spandidos, 2013)
Prostate cancer stem-like cells (PCSLCs) are considered to be the ‘seed’ of prostate cancer. The aim of this study was to confirm that the PC-3 cells, which we isolated and enriched from PC-3 cells through magnetic bead cell sorting (MACS) and serum-free medium (SFM) culture, were PCSLCs. Combinations of MACS, flow cytometry (FCM), SFM and immunocytochemistry (ICC) were used to ensure the positive expression of CD133 and CD44 on PC-3 and sphere-forming cell membranes. Self-renewal, multi-potential differentiation, unlimited proliferation and permanency assays were also applied to indentify whether the PC-3 cells exhibited the characteristics of cancer stem cells (CSCs). As a result, there was a low proportion of PCSLCs in the PC-3 cells. In the FCM assay, the proportion of cells expressing CD133 or CD44 in the PC-3 cells was 0.51 and 0.31%, respectively. In addition, we found that the proportion of PC-3 cells sorted by MACS that expressed CD133 was significantly increased compared with that of the sphere-forming cells cultured in SFM (99.09 vs. 84.80%, P<0.05), while no difference was observed in the proportion of cells expressing CD44 between them (99.88 vs. 99.82%, P>0.05). The expression of PAP and AR as detected by western blot analysis of induced PCSLCs was significantly increased compared with that of uninduced PCSLCs (P<0.05); the proliferation capacity of PCSLCs was significantly higher than that of both the PC-3 cells (P<0.05) and induced PCSLCs (P<0.05). Furthermore, the PCSLCs that were isolated from SFM and MACS both demonstrated certain characteristics of stem cells and should be considered as stem cell-like. These data may hold potential for further exploring the role of PCSLCs.